Lipopolysaccharide (LPS) exposure differently affects allergic asthma exacerbations and its amelioration by intranasal curcumin in mice. Issue 2 (December 2015) - Kumari, Asha; Dash, D.; Singh, Rashmi
Highlights Dose and schedule of LPS exposure determines asthma exacerbations. Lower dose of LPS exposure is better in exacerbating allergic asthma. Enhanced airway inflammations are dominated by eosinophils and neutrophils. Th2 cytokine and IgE levels are enhanced after LPS exposure. Intranasal curcumin is better in ameliorating the exacerbations than dexamethasone.